2022
DOI: 10.3389/fenvs.2022.1021596
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater contamination through potentially harmful metals and its implications in groundwater management

Abstract: Groundwater contamination through potentially harmful metals (PHMs) is an environmental hazard in Pakistan with significant human health risk reports. The current research was conducted in Sheikhupura District, which is a major industrial site in Punjab, Pakistan. According to the Punjab Directorate of Industries in Pakistan, there are a total of 748 industries in this area. These industries produce a lot of waste and effluent, which contaminate the environment with harmful and toxic materials. Continuous irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…All the mean values exceeded the acceptable limit (0.02 mg/L) set by FMEnv (2011). This could be attributed to geogenic effect exacerbated by anthropogenic effects especially in wells 2 and 4 (Ullah et al, 2022). Geogenic contamination is the natural occurrence of some elements in groundwater at elevated levels above acceptable limits with potential of adverse health effect (CGWB, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…All the mean values exceeded the acceptable limit (0.02 mg/L) set by FMEnv (2011). This could be attributed to geogenic effect exacerbated by anthropogenic effects especially in wells 2 and 4 (Ullah et al, 2022). Geogenic contamination is the natural occurrence of some elements in groundwater at elevated levels above acceptable limits with potential of adverse health effect (CGWB, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Spatial variations in major ions were analyzed statistically and are presented in Table 1 and Figures [8][9][10][11][12][13][14][15][16][17][18]. Spatial mapping was accomplished using the inverse distance weighting (IDW) tool within ArcGIS 10.8, which assumes the proximity rule.…”
Section: Spatial Variation Of Major Ionsmentioning
confidence: 99%
“…In the eastern and central areas of Punjab, the elevated As concentration is attributed to higher soil pH levels (8.0-8.5), which are prevalent throughout the Indus Plane [44]. Due to the soil's higher pH, As desorption is triggered in the upper soil layers, and subsequently, leaching occurs down to the groundwater [23,27]. In Southern Punjab, however, aridity is the dominating cause of the elevated As levels, resulting from higher evaporation rates [45].…”
Section: As Concentration In the Groundwater Of Punjabmentioning
confidence: 99%
“…When ingested, As can cause serious health consequences such as cardiovascular damage, neurological effects, oxidative stress, enzyme inhibition, and development abnormalities [21]. Several studies have reported elevated levels of As in the country's groundwater resources, ranging from 10 ppb to 600 ppb, which significantly exceed the standards set by the World Health Organization [23][24][25][26][27]. For instance, ref.…”
Section: Introductionmentioning
confidence: 99%